Research theoretical and experimental model solar adsorption refrigerator using Zeolite - Water - Hoang, An Quốc; Tran, Văn Vang; Le, Chí Hiệp; Quang, Thị Cẩm Thì (Journal of Technical Education Science, 2014)
This article presents the results of theoretical and experimental research model solar adsorption refrigerator using Zeolite-water, this machine can be used for different purposes such as preserving fruits and vegetables, food or air conditioning ... The commissioning data of this model is taken in November 2012 in district 7 Ho Chi Minh city. The experimental results show that the solar collector performance gain index range ht = 5,3 ¸ 6,9% and cooling performance of the machine is achieved value hl = 4,02 ¸ 6,02%. Although the radiation intensity is relatively low but with achieved effective of system on which means the solar adsorption refrigerator using Zeolite-water can apply in practice if it is studied, improved and carried out at the time points higher radiation intensity.